2023
DOI: 10.3390/s23156690
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Systems and Deep Learning for Safety and Health Activity Monitoring on Construction Sites

Abstract: Construction is a highly hazardous industry typified by several complex features in dynamic work environments that have the possibility of causing harm or ill health to construction workers. The constant monitoring of workers’ unsafe behaviors and work conditions is considered not only a proactive but also an active method of removing safety and health hazards and preventing potential accidents on construction sites. The integration of sensor technologies and artificial intelligence for computer vision can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…The challenges during safety management in the construction sector have been a significant source of concern for both researchers and practitioners. Studies have revealed that unsafe acts and unsafe working conditions account for more than 90% of accidents on construction job sites [36]. The accident rate has not decreased despite the provision of safety regulations, i.e., OSHA, HSE, ISO 18000.…”
Section: Resultsmentioning
confidence: 99%
“…The challenges during safety management in the construction sector have been a significant source of concern for both researchers and practitioners. Studies have revealed that unsafe acts and unsafe working conditions account for more than 90% of accidents on construction job sites [36]. The accident rate has not decreased despite the provision of safety regulations, i.e., OSHA, HSE, ISO 18000.…”
Section: Resultsmentioning
confidence: 99%
“…Computer vision holds great promise in enhancing workplace safety through AI applications. 104 It enables various functions, including monitoring employee conduct, identifying potential risks, and issuing real-time alerts. An excellent example of its implementation is the use of thermal cameras to identify heat stress in workers.…”
Section: Ai and Occupational Safety Enhancementsmentioning
confidence: 99%
“…The application of AI in construction management, in general, can aid in optimizing [14], [15] and automating [4] various construction management tasks. This includes project scheduling, delay analysis, Work Breakdown Structure (WBS) creation, project budgeting, updating project progress and schedules, identifying deviations, creating risk maps, and team member allocation [16]- [18].…”
Section: Application Of Ai In Construction Managementmentioning
confidence: 99%